Predicting Sudden Deaths Following Myocardial Infarction in Malaysia Using Machine Learning Classifiers - Halim M.H.A.; Yumn Suhaylah Yusoff; Mazlynda Md Yusuf (Science Publishing Corporation Inc, 2024)
Indexed by SCOPUS/ERA